Graphitic Petal Micro‐Supercapacitor Electrodes for Ultra‐High Power Density. Issue 11 (22nd October 2014) - Xiong, Guoping; Meng, Chuizhou; Reifenberger, Ronald G.; Irazoqui, Pedro P.; Fisher, Timothy S.
Abstract High‐power micro‐supercapacitors based on micrometers‐thick graphitic petal electrodes have been designed and fabricated. The electrodes were prepared by using microwave plasma chemical vapor deposition and patterned by optical lithography and reactive ion etching. Charge/discharge rates up to 100 000 mV s−1 (1000 times faster than conventional supercapacitors) have been achieved in 1 M H2SO4 aqueous electrolyte. After electrochemical oxidization treatment in 1 M H2SO4 solution at room temperature, a volumetric capacitance of 270 F cm−3 (with an area‐normalized capacitance of 108 mF cm−2) was observed at a scan rate of 20 mV s−1 while maintaining high charge/discharge rates. The electrochemically treated microdevices exhibit energy densities in the range of 0.8 to 10 mWh cm−3, power densities in the range of 0.6 to 235 W cm−3, a theoretical maximum power density of 292 W cm−3 at a current of 100 μA, and good cycling stability.